Design of differential pressure type gas drainage flow meter with dynamic compensatio - YANG Xujun; WANG Wenlong; GAO Wenping; ZHU Chengjia (Gong-kuang zidonghua, 2015)
In view of problem of large flow measurement error caused by existing gas drainage flow meter which cannot realize real-time compensation for pipeline flow parameters, a differential pressure type gas drainage flow meter with dynamic compensation was designed. The compensation methods of gas temperature, pressure and concentration were gave, and design schemes of hardware and software of the flow meter were introduced. The field test results show that the flow meter meets accuracy requirement of coal mine gas drainage measurement with accurate and stable data.